Investigation of the starch-binding properties of wheat friabilin - Csóti, István (Acta Biologica Szegediensis, 2005)
The genes of two wheat proteins related to the texture of the grain, puroindoline A and grain softness protein 1, were cloned and expressed in Escherichia coli. Starch binding properties of the heterologously expressed proteins were studied in vitro. Both proteins bind to starch similarly to nativ friabilin prepared from soft wheat flour, and thus they are likely to be properly folded.